Investigation of gamma irradiation effects on the properties of CdS/p-Si heterostructure. (April 2019) - Ali, Syed Mansoor; Ramay, Shahid Mehmood; Rehman, Naeem Ur; ALKhuraiji, Turki S.; Shar, Muhammad Ali; Mahmood, Asif; Hassan, Ather; Riaz, Muhammad
Abstract: Cadmium sulfide (CdS) thin films were deposited on p-type Si substrate by thermal evaporation to fabricate the CdS/p-Si heterojunction. Gamma irradiation has been used to modify the microstructural, optical and electrical characteristics of CdS/p-Si heterojunction of various doses in the range (0–80 kGy). X-ray diffraction measurements of the gamma irradiated show the reduction in crystallinity of the CdS thin films. While scanning electron microscope images depicted the average CdS particle size was found to be increased with increasing the gamma irradiation dose. Photoluminescence results revealed that at the specific dose of gamma irradiation was found to create the yellow emission in interstitial sites to the valence band. The I–V characteristics showed the current transport properties effected by the different gamma doses. The values of barrier height, saturation current and ideality factor for the CdS/p-Si heterostructure varied due to the causes like inhomogeneities in the interfacial, defect density, charge distribution on interfacial and interfacial layer thickness after gamma irradiation. The gamma irradiation induced effects and the possible mechanism in CdS/p-Si heterojunction is discussed.